Maternal–fetal safety evaluation of an aqueous extract of Casearia sylvestris leaves in rats - Nagaoka, Livia Trippe [UNESP]; Jorge, Bárbara Campos [UNESP]; Stein, Júlia [UNESP]; Manoel, Beatriz de Matos [UNESP]; Valente, Leticia Cardoso; de Toledo, Laura Leonel [UNESP]; de Castro, Thiago Luis Aguayo; Kassuya, Cândida Aparecida Leite; Cardoso, Claudia Andrea Lima; Arena, Arielle Cristina [UNESP] (Wiley, 2023)
Background: This study evaluated the maternal, embryotoxic, and teratogenic effects of the aqueous extract of Casearia sylvestris (AECS), a species listed in the Unique Health System of Brazil, and widely used for treating several conditions, such as diarrhea, wounds, pain, and ulcers. Methods: Pregnant rats were daily treated orally with 0, 175, 350, or 700 mg/kg/body weight of AECS, from gestational day (GD) 6 to 15 (organogenesis period). On GD 20, the pregnant rats were euthanized, and the litters submitted to an assessment of fetal development. Results: No clinical signs of toxicity were observed in the dams during the treatment. In the embryo-fetal development study, a significant increase in the basal zone height of the placenta was observed in the intermediate dose group. Furthermore, there was a significant increase in the relative anogenital distance measurement of female fetuses in the lowest and intermediate dose groups. Although no visceral abnormalities were observed in the treated-fetuses, skeletal anomalies evidenced by changes in the ossification of the sternum and the presence of supernumerary ribs were found in the intermediate and high dose groups. Conclusion: In conclusion, the treatment with AECS during organogenesis at this dose level had detrimental effects on the normal development of fetuses.
Keywords: medicinal plants; pregnancy; rats; safety; skeletal abnormalities; teratogenicity